Development and Validation of HPTLC Method for Estimation of Glycyrrhizic Acid in Herbal Formulation - Ahmad*, Sayeed; Kamal, Y.T.; Singh, Mhaveer; Parveen, Rabea (Asian Journal of Chemistry, 2011)
A simple, accurate, selective, precise and economical high performance thin layer chromatographic method was developed on silica using solvent system chloroform:glacial acetic acid:methanol:water in the ratio of 60:32:12:8 at 254 nm wavelength in absorbance mode for the analysis of glycyrrhizic acid in crude drugs as well as in herbal dosage form. The solvent was found to give well defined, compact and sharp peak of glycyrrhizic acid at Rf 0.28 ± 0.02. Method was validated for accuracy, precision and specificity. It shows good linearity in the range of 100-500 ng/spot (r2 = 0.9908) with slope and intercept 2802.03 and 31.06, respectively. The method found to be precise (RSD % < 3) and accurate (recovery 99-102 %). The proposed method was applied for quantitative estimation of glycyrrhizic acid in a solid herbal formulation consisting of powdered roots of Glycyrrhiza glabra, which showed the presence of glycyrrhizic acid in formulation in the range of 0.030-0.055 % w/w. The proposed method found simple and economic to be used in general laboratory conditions for quality control of crude drugs and herbal formulations.